Semantic Foundations of Reductive Reasoning. - Gheorghiu, Alexander V.; Pym, David J. (Topoi: An International Review of Philosophy, 2026)
The development of logic has largely been through the deductive paradigm: conclusions are inferred from established premisses. However, the use of logic in the context of both human and machine reasoning is typically through the dual reductive perspective: collections of sufficient premisses are generated from putative conclusions. We call this paradigm, reductive logic. This expression of logic encompass as diverse reasoning activities as proving a formula in a formal system to seeking to meet a friend before noon on Saturday. This paper is a semantical analysis of reductive logic. In particular, we provide mathematical foundations for representing and reasoning about reduction operators. Heuristically, reduction operators may be thought of as 'backwards' inference rules. In this paper, we address their mathematical representation, how they are used in the context of reductive reasoning, and, crucially, what makes them valid.